The Impact of Astaxanthin Supplementation on the Lipid Profile - Arczewski, Filip; Wójcikiewicz, Michalina; Czyż, Witold; Kacperczyk, Julia; Dziedzic, Karol; Chuncia-Ileczko, Marta; Wojszczyk, Maciej; Zys, Damian; Pasek, Piotr; Ryniecka, Julia; et al. (Quality in Sport, 2025)
Astaxanthin (AST) is a carotenoid renowned for its strong antioxidant properties and its role as a pigment in various aquatic organisms. Initially isolated from lobster and subsequently characterized in detail, AST has garnered significant interest in recent years within the research, pharmaceutical, cosmetic, and supplement industries. This review aims to synthesize current literature on the impact of astaxanthin supplementation on lipid profiles, specifically focusing on low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides. Evidence suggests that AST effectively prolongs the oxidation lag time of LDL, thereby mitigating the risk of atherosclerosis and cardiovascular diseases through its antioxidative mechanisms. The effects of AST on HDL-C levels are less consistent, with some studies reporting modest increases while others show no significant changes. Similarly, the influence of AST on triglyceride levels remains inconclusive, with studies presenting mixed outcomes ranging from significant reductions to negligible effects. AST is characterized by a high safety profile and favorable bioavailability, which is influenced by its source and isomeric composition. Despite these promising findings, many existing studies are limited by small sample sizes, heterogeneous participant groups, and varied dosing regimens, which impede the ability to draw definitive conclusions. Consequently, there is a need for larger, well-standardized clinical trials to accurately assess the efficacy and safety of astaxanthin as a therapeutic agent for lipid modulation and the prevention of metabolic disorders. Future research should focus on robust methodological designs and standardized supplementation protocols to clarify AST’s role in managing dyslipidemia and enhancing cardiovascular health.